QUALITY OF LIFE OF THE ELDERLY IN DISASTER-PRONE AREAS - Norman Wijaya Gati; Dita Mirawati; Rita Tri Subekti (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Background: Elderly individuals are inherently vulnerable, facing a decline in physical and cognitive functions that significantly impacts their quality of life (QoL). QoL is a vital, multidimensional concept influenced by physical health, psychological state, independence, social relationships, personal beliefs, and environment. A good QoL enables the elderly to enjoy life, maintain independence, and feel respected. However, disaster conditions, such as floods, are high-risk, unexpected events that drastically affect QoL by causing loss, physical injury, and psychological trauma. Songgorunggi Village, Sukoharjo, Central Java, is a known flood-prone area that suffered significant impact in 2024. Despite this, some elderly residents have demonstrated adaptive and resilient coping mechanisms. The purpose of this study was to describe the quality of life of the elderly in this disaster-prone region. The method employed a descriptive analytical research design utilizing the established WHOQOL quality of life questionnaire. The results indicated that the majority of the elderly participants in the Songgorunggi area were female, and a significant percentage—65.5%—reported a poor quality of life. In conclusion, the QoL of the elderly residing in the disaster-prone area of Songgorunggi village was categorized across both the good and poor spectrums, with a substantial majority falling into the poor category following the disaster